LEPROSY AND HUMAN IMMUNODEFICIENCY VIRUS COINFECTION: A RARE CASE REPORT - lydiawati, eva; Sirithida, Chukmol; Vannda, Sou; Vortey, Hak; Ratana, Heng; Listiawan, M. Yulianto; Agusni, Indropo (Institute of Topical Disease Universitas Airlangga, 2019)
Leprosy, or Hansen disease, is a chronic infectious disease caused by Mycobacterium leprae which is associated with inflammation that may damage the skin and the peripheral nerves. Leprosy remains an important public health problem in Southeast Asia, America, and Africa. It has been speculated that, as with TB, HIV infection may exacerbate leprosy lesions and/or lead to increased susceptibility to leprosy. We report the case of leprosy and HIV co-infection and reveals its clinical manifestation. A 34-year-old female came to outpatient clinic complaining of rednessplaque on her face of 2-months duration. It was also accompanied with thick sensation but without itchy or burning sensation. We found thick erythematous plaque with sharp margin and hypoesthesia on her face and body. There were no madarosis, saddle nose, lagophthalmos, nor sign of neuritis. The slit-skin smear revealed BI 1+ globi and MI 2%. From laboratory examination we found CBC was within normal limit, IgM anti PGL-1 titer was 1265 u/mL and IgG anti PGL-1 was 834 u/mL Both histological examination on her ear lobe and extremity revealed that was similar to the lesion of leprosy. The detection of HIV antibody was positive with CD4 count on 325 cells/Î¼L. We treat her with MDT for MB leprosy along with ART (Tenofovir, Lamivudine, and Efavirenz). After 6-months follow-up we observed no progression of the lesions though the slit-skin smear after completing 6 months of therapy become negative. M. leprae does not seem to accelerate the decline of immune function when associated with HIV infection. HIV infection does not seem to affect the clinical classification and progression of leprosy. Treatment of the HIV-leprosy co-infected patient consists of the combination of ARTs and anti-leprosy agents. So that, the treatment of leprosy and HIV co-infection does not differ from that of a seronegative leprosy patient.